Stakeholders wanted! Why and how European Union agencies involve non-state stakeholders. Issue 9 (2nd September 2018) - Arras, Sarah; Braun, Caelesta
ABSTRACT: This article examines why and how European Union agencies involve non-state stakeholders – such as non-governmental organizations (NGOs), business associations or trade unions – via three access instruments: public consultations; stakeholder bodies; and representation in management boards. We assess how the use of these instruments varies across agencies, and how they are linked to different motivations driving the demand for stakeholder participation. We present two alternative sets of hypotheses, first focusing on agencies' need for information, organizational capacity and reputation, and second, considering stakeholder involvement as an instrument of legislative control. We draw on a new dataset of stakeholder involvement practices of the full population of EU agencies, compiled via document analysis and interviews. Our findings indicate that stakeholder involvement is a double-edged sword, contributing to agency accountability and control, but with an inevitable risk of dependence on the regulated industry.